Isolation and cultivation of the genus chaetoceros from coastal water of Pahang for lipid compound analysis - Mohamad Fuad bin Mohamad Anuar (Kulliyyah of Science, International Islamic University Malaysia, 2014)
This study is aimed to study the morphology and to analyze the production of fatty acids from few marine algae under the Genus Chaetoceros isolated from Coastal Water of Pahang, Malaysia. The algae were established into cultured using f/2 media and identified using light microscope (LM) and scanning electron microscope (SEM). Lipid profile for each species was determined at every growth phase (exponential, stationary and death) by using GCMS. Statistical analysis of one-way anova was conducted to evaluate the significant and homogeneity data on the growth of each alga obtain and total lipid obtained. Results showed that four species were successfully cultivated and identified as Chaetoceros baculites, Chaetoceros anastomosans, Chaetoceros affinis var. willei and Chaetoceros affinis var. affinis. All morphological features of these species are agreeable with previous descriptions except for several characteristics of C. anastomosans and C. baculites. New information obtained is the aperture opening C. anastomosans and data on the size of aperture, the terminal setae and spine arrangement of C. baculites. C. baculites has the highest growth rate (0.72 cell.day-1) and division's value (1.08) while C. anastomosans has highest doubling time value (8.66). Statistical analysis showed that all species has significantly different growth rate (P<0.05). Eight fatty acids were detected from species studied. Myristic acid was the main component for lipid storage for C. baculites, C. anastomosans and C. affinis var. willei whereas palmitic acid for C. affinis var. affinis. All species contained about 35% to 75% of total percentage fatty acids in all growth phases. Based on total percentage, both affinis varieties have high lipid percentage compared to other two species with the total percentage more than 70%. As a conclusion, all these species are suitable to be used in lipid industry in Malaysia with C. affinis var. affinis is the best candidate for lipid industry due to health safety and high lipid production.